Transformative social science? Modes of engagement in climate and energy solutions. (August 2018) - Haarstad, Håvard; Sareen, Siddharth; Wanvik, Tarje I.; Grandin, Jakob; Kjærås, Kristin; Oseland, Stina E.; Kvamsås, Hanna; Lillevold, Karin; Wathne, Marikken
Abstract: The social sciences are increasingly called upon to engage with how decision-makers and stakeholders tackle climate and energy challenges. However, creating or taking part in these new arenas is not unproblematic, and arguably, social scientists have not properly reflected on what types of engagement are most useful. In this Perspective we argue that such engagement is most productive if we can find or create activities where our core competences, epistemological toolbox and critical sensibilities can be put to use. Therefore, we propose three modes through which social science can productively engage with climate and energy challenges in society: (1) producing and situating actionable knowledge, (2) critically reframing discourses, and (3) connecting actors and processes. Combined, these open up a space for social scientists to both critically assess and simultaneously participate in sustainability transformations.